A holistic green system coupling hydrogen production with wastewater valorisation. Issue 6 (28th June 2022) - Jiang, Lixue; Pan, Jian; Li, Qiyuan; Chen, Han; Zhou, Shujie; Yu, Zhichun; Jiang, Shuaiyu; Yin, Huajie; Guan, Jing; Taylor, Robert A.; Fisher, Ruth; Leslie, Greg; et al.
Abstract: Green hydrogen represents a critical underpinning technology for achieving carbon neutrality. Although researchers often fixate on its energy inputs, a truly 'green' hydrogen production process would also be sustainable in terms of water and materials inputs. To address this holistic challenge, we demonstrate a new green hydrogen production system which can utilize secondary wastewater as the input (preserving scarce fresh water supplies for drinking and sanitation). The enabling feature of the proposed system is a self‐grown bifunctional CoNi electrode which consists of ultrathin, spontaneously deposited CoNi nanosheets on a three‐dimensional nickel foam. As such, a green synthesis process was developed using an immersion procedure at room‐temperature with zero net energy input. Testing revealed that the synthesized CoNi electrodes can reach a current density of 10 mA cm −2 at a small overpotential of 197 mV for the hydrogen evolution reaction and 315 mV for the oxygen evolution reaction in alkalified wastewater. The values are 16.5% and 6.5% smaller than that from precious catalysts (20 wt% Pt/C and RuO2, respectively). Importantly, this CoNi catalyst offers outstanding durability for overall wastewater splitting. A prototype solar‐energy‐powered rooftop wastewater splitting system was constructed and can produce more than 100 L hydrogen on a sunny day in Sydney, Australia. Taken together, these results indicate that it is promising to unlock holistically green routes for hydrogen production by wastewater uplifting with regards to water, energy, and materials synthesis. Abstract : A holistic green system is proposed for sustainable hydrogen production and wastewater valorisation. The utilization of the pre‐treated wastewater avoids the sophisticated water purification process, the electrode fabrication process involves no net energy input and is carbon neutral, and the photovoltaic cell transforms solar energy to electricity and ensures low‐cost and green hydrogen production.